STRATEGI PENGEMBANGAN KOPERASI DI KABUPATEN BATANG - MUKH ISNANTO (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2018)
Cooperative is a business entity that consists of people or legal entities that carry out its activities based on the principle of cooperatives as well as the economic movement of the people based on the family principle. Cooperatives have a major role in the Indonesian economy because the cooperative is moving the socio-economic.The cooperative state is so strategic that it needs to be the focus of economic development in Batang district. Now it takes a strong commitment to build a cooperative that can help itself in accordance with the identity of the cooperative. The role of cooperatives, very strategically in the economy in the Batang district, so needs to be the focus of economic development in the future. The empowerment of cooperative and sustainable cooperatives is expected to harmonize the structure of national economy, accelerate national economic growth, reduce open unemployment, decrease poverty, Dynamization of the real sector, and improve community revenue equality. Cooperative empowerment will also increase the achievement of targets in education, health, and indicators of other Indonesian community welfare. The role of cooperative in the economy in Batang district can be seen from his position as a major player in economic activity across sectors, the largest job provider, a crucial player in the development of local economic activities and Community empowerment, New Market creator and source of innovation, and its contribution in maintaining balance of payments through export activities